Multi-spatial co-distribution of the endangered Ladakh urial and blue sheep in the arid Trans-Himalayan mountains - Namgail, T.; van Wieren, S.E.; Mishra, C.; Prins, H.H.T. (Journal of arid environments, 2010)
Large wild herbivores are important ecologically and economically, and maintaining their populations is a crucial management concern. The Ladakh urial Ovis vignei vignei is an endemic and endangered wild sheep inhabiting the arid Trans-Himalayan region of Ladakh, where its population is restricted to narrow tracts along two river valleys. The causes of this restricted distribution of the species are not understood. We asked if competitive exclusion by the more abundant wild ungulate, the blue sheep Pseudois nayaur, could explain the limited range of Ladakh urial. To explore this possibility we studied the occurrence patterns of these two species at multi-spatial scales (regional, landscape and habitat). We found that they occurred independently at the regional scale, but co-occurred at the landscape scale, facilitated by divergence in seasonal resource use at the habitat scale. Although the two species segregated along both habitat and diet axes during summer at the habitat scale, there is a high potential for competition during winter, the ‘pinch’ period, when they overlap in their habitat use due to altitudinal migration. Therefore, the presence of blue sheep seems to limit the population growth and range expansion of the Ladakh urial.